2021
DOI: 10.26444/aaem/122628
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor in gastroenterology oncology – short review of current literature

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophins group which plays a crucial role in brain development and neurogenesis. In the hypothalamus it is described as playing a role in energy metabolism and feeding behaviour. The hippocampal concentration of BDNF is believed to play an important role in learning and memory, it has a protective role in neurodegeneration and stress responses. BDNF is also known to take part in many other processes, e.g. angiogenesis, proliferation, cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, studies showed that BDNF plays a crucial role in neurodegenerative disorders. Apart from neurodegenerative disorders, the importance of BDNF in many other diseases such as diabetes and cancer was also investigated [1,119]. However, limited studies showed the BDNF-miRNA interactions and the modulation of BDNF signaling by miRNAs.…”
Section: Concluding Remarks and Limitationsmentioning
confidence: 99%
“…Moreover, studies showed that BDNF plays a crucial role in neurodegenerative disorders. Apart from neurodegenerative disorders, the importance of BDNF in many other diseases such as diabetes and cancer was also investigated [1,119]. However, limited studies showed the BDNF-miRNA interactions and the modulation of BDNF signaling by miRNAs.…”
Section: Concluding Remarks and Limitationsmentioning
confidence: 99%
“…We discussed the alteration of BDNF level and BDNF-based therapies in different disease models. Apart from the disorders above mentioned, the role of BDNF was also investigated in many other diseases such as diabetes and cancer ( Eyileten et al, 2017 ; Guzel et al, 2021 ). Understanding the role of BDNF and its signaling as well as how they regulate repair or regrowth of CNS will be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that BDNF plays a role in growth, invasion, and metastasis in several types of tumors, such as gastric cancer, lung cancer, hepatocellular carcinoma, and ovarian and prostate cancers. The BDNF binds to tropomyosin-related kinase B (TrkB) receptor and triggers the production of pro-migratory, pro-survival, and anti-apoptotic proteins 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%